Effect of polypropylene fiber content on flexural strength andelastic modulus of concrete - Nguyen , Huy Vững; Do, Văn Dũng; Le , Thế Sang (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
The aim of the study is to find out the effects of polypropylene fiber content on the flexural strength and elastic modulus of concrete, and to evaluate the relationship between polypropylene fibers and the flexural and elastic modulus of the concrete. concrete, the applicability of concrete with the addition of polypropylene fiber reinforcement in the concrete structure, evaluation of the working ability of the concrete mixture with the addition of polypropylene fibers when supplemented with silicafume byproducts. Materials used to design the mix with variable content: polypropylene fiber with 0% content; 0.5%; 1.0%; 1.5% and 2% by volume of concrete, proportion of silicafume by-products by weight of cement, sand, stone, cement, plasticizer admixture 1.5% and control mix. Graded concrete with by-product reinforcement reaches durability grade B25. The study was carried out using experimental materials available in Vietnam. Research results show that concrete using polypropylene fibers has the ability to increase flexural strength, and at the same time, using silicafume additives will make the fibers have better adhesion in concrete, and the flexural strength of the samples. indirect experiments were higher.